The Existence And Relevance of The Main Poins of State Direction In The Constitutional System According to UUDNRI 1945 - Hardjanti, Dewi Krisna; Hartono, Yohanes (DAS Institute, 2025)
This paper discusses the urgency and implications of The Main Poins Of State Direction In The Constitutional System (PPHN) in Indonesian state administration where after the MPR no longer has the authority to determine the Guidelines of State Policy (GBHN), the GBHN function is replaced by Law Number 25 of 2004 concerning the National Development Planning Systems and Law Number 17 of 2007 concerning the National Long-Term Development Plan (RPJPN) 2005-2025. This has an impact on the Indonesian state administration ideologically, juridically, and politically. The research method in this study uses the normative juridical method. In conclusion, the preparation of PPHN is something that has become a necessity for Indonesia today and the implementation of PPHN will not have adverse implications for the Indonesian Presidential system of government, it will even strengthen the Presidential system. In addition, the existence of PPHN actually complements the perfection of Indonesia's constitutional building, namely Indonesia has Pancasila as the ideology and foundation of the state, The 1945 Constitution of Republic Indonesia (UUDNRI 1945) as the constitutional direction of the state, and PPHN as the basic policy of state development. The results of the study show that this GBHN needs to be elaborated into stages that can facilitate efforts to achieve it. To provide a legal basis, the direction of the State (whatever its name) needs to be outlined in legal form